Incentives to Motivate - Ola Kvaløy; Anja Schöttner (Center for Economic Studies and ifo Institute (CESifo), 2014)
We present a model in which a motivator can take costly actions - or what we call motivational effort - in order to reduce the effort costs of a worker, and analyze the optimal combination of motivational effort and monetary incentives. We distinguish two cases. First, the firm owner chooses the intensity of motivation and bears the motivational costs. Second, another agent of the firm chooses the motivational actions and incurs the associated costs. In the latter case, the firm must not only incentivize the worker to work hard, but also the motivator to motivate the worker. We characterize and discuss the conditions under which monetary incentives and motivational effort are substitutes or complements, and show that motivational effort may exceed the efficient level.
Keywords: D86; J33; M52; 330; incentives to motivate